Effect of restricted geometry on structural phase transitions in KH2PO4 and NH4H2PO4 crystals - Tarnavich, Vladislav; Korotkov, Leonid; Karaeva, Olja; Naberezhnov, Alexander; Rysiakiewicz-Pasek, Ewa (Oficyna Wydawnicza Politechniki Wrocławskiej, 2010)
The dielectric response of crystalline NH4H2PO4 and KH2PO4–SiO2 and NH4H2PO4–SiO2 composites prepared by embedding salts into porous glasses with the average pore diameter of 320 nm has been studied at the temperature range of 85–300 K. An increase of the structure phase transition temperatures in embedded salts has been observed, which is supposedly due to tensile deformations of embedded crystalline particles. The antiferroelectric phase transition in confined ADP particles becomes diffuse in the temperature region around 10 K.
Optica Applicata, Vol. 40, 2010, nr 2, s. 305-309
Keywords: optyka; ferroelectrics; antiferroelectrics; composite materials; porous glass; phase transition; dielectric permittivity